Robots - Wedge, Chris; Davis, Jerry; Donkin,John C.; Joyce, William (Twentieth Century Fox Home Entertainment ; distributed in the Philippines by Viva Video, 2005)
A young inventor embarks on a journey to attempt a position in a company run by his idol, master inventor Bigweld, along the way he encounters new and old robot friends who help him battle to keep his position in the company.